Growth patterns and reproductive performance of grazing Brahman cows in a tropical environment - Vera, Raúl R.; Ramírez, C.A.; Velásquez, N. (2002)
Two experiments were conducted in the neotropical savannas of Carimagua, Colombia to test the hypothesis that Brahman females subjected to sustained grazing undernutrition as heifers can attain high reproductive performance as mature cows if allowed to make compensatory gains. In Experiment 1, weaned heifers were subjected to three rates of weight gain (H, M and L) on a poor quality tropical pasture until reaching mating weight of 270 kg. Each group was then subdivided and grazed on pastures that allowed high (h) or low (l) weights gains. Experiment 2 allowed heifers of the same type to achieve continuous high weight gains and served as a control. Regardless of earlier treatment, all h cows in Experiment 1 achieved mature body size and reproductive performance comparable to those of the well-fed animals of Experiment 2. It is concluded that the potential exists for a wide range of grazing managements of Brahman heifers in the tropics, and it is possible to achieve levels of performance that represent a substantial improvement over current standards at a modest management cost.